When Peace is Personalized: The Clash between the BoP Charter and Indonesia’s Free and Active Foreign Policy - Natamiharja, Rudi; Kurniawan, Robi Cahyadi; Kpanya, Ovide Egide Manzanga; Ablin, Rainnade Geojona (Uti Possidetis: Journal of International Law, 2026)
Background: This article critically examines the legal and constitutional implications of Indonesia’s engagement with the "Board of Peace" (BoP), an emerging ad hoc entity in global peace governance. It highlights the systemic tension between established multilateral frameworks and the BoP’s "Chairman-centric" model, which represents a shift from rule-based to person-based international authority. Methodology: This study employs a normative legal research method to compare the BoP Charter, the United Nations Charter, and Indonesia’s domestic legal framework. Objectives: The research, aims to evaluate the compatibility of the BoP’s centralized governance with the principles of sovereign equality, modern multilateralism, and Indonesia’s constitutional mandate of a "Bebas Aktif" (free and active) foreign policy. Findings: The analysis reveals that the BoP’s institutional design—characterized by unfettered discretionary power vested in a single office—breaks the "chain of democratic delegation" required by Article 1 of the 1945 Indonesian Constitution. Furthermore, it risks creating "functional subordination" that undermines Law No. 37 of 1999 on Foreign Relations. Conclusion: Consequently, the study argues that Indonesia should utilize the period prior to ratification as a "constitutional firewall" to protect its strategic autonomy and domestic legal integrity. Novelty: This research provides a pioneering analysis of the BoP Charter through the lens of Indonesian constitutionalism, offering a critical perspective on how middle powers in the Global South should navigate ad hoc governance initiatives that bypass traditional UN-centric multilateralism.